Transcomplementation by a Truncation Mutant of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Enhances ΔF508 Processing through a Biomolecular Interaction - Cebotaru, Liudmila (American Society for Biochemistry and Molecular Biology, 2013)
We previously showed that a truncation mutant of CFTR missing the first four transmembrane segments of TMD1, Δ264 CFTR, binds to key elements in the ER quality control mechanism to increase the amounts of the mature C band of both wt and ΔF508 CFTR through transcomplementation. Here, we created a new construct, Δ27–264 CFTR. Even though Δ27–264 CFTR is rapidly degraded in the proteasome, steady state protein can be detected by Western blot. Δ27–264 CFTR can also increase the amounts of the mature C band of both wt and ΔF508 CFTR through transcomplementation. Electrophysiology experiments show that Δ27–264 CFTR can restore chloride channel currents. Further experiments with the conduction mutant S341A show conclusively that currents are indeed generated by rescued channel function of ΔF508 CFTR. Immunoprecipitation studies show that Δ27–264 binds to ΔF508-CFTR, suggesting a bimolecular interaction. Thus the adeno-associated viral vector, rAAV-Δ27–264 CFTR, is a highly promising CF gene therapy vector, because it increases the amount of mature band C protein both from wt and ΔF508 CFTR, and rescues channel activity of ΔF508 CFTR.